2022
DOI: 10.3390/separations9020036
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Volatiles in Senecio anteuphorbium Essential Oil with a Focus on Its Allelopathic Effect by Means of Gas Chromatography

Abstract: The present study aimed to investigate Senecio anteuphorbium, an endemic plant growing in West Morocco and widely used in local folk medicine. The essential oil (EO) extracted from the aerial parts was analyzed by gas chromatography and tested for allelopathic activity. The quantitation of the volatiles was carried out by means of GC-FID with response factors, which were validated through reliable calibration procedures, based on external and internal standardization. This analytical approach allowed to define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The coagulation efficiency obtained varies at certain doses as a function of pH and might be explained by the bridging mechanism, in which the coagulant and the particle carry the same surface charges, which involves the adsorption of coagulant segments on adjacent colloidal surfaces, thus linking them each other (Bolto & Gregory, 2007). It has been reported that S. anteuphorbium contains a major component on hydrocarbons, cellulose followed by alcohols, ketones, and aldehydes (Ouhaddou et al, 2022). According to the literature, hydrocarbons and some cellulose derivatives are characterized as nonionic polymers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coagulation efficiency obtained varies at certain doses as a function of pH and might be explained by the bridging mechanism, in which the coagulant and the particle carry the same surface charges, which involves the adsorption of coagulant segments on adjacent colloidal surfaces, thus linking them each other (Bolto & Gregory, 2007). It has been reported that S. anteuphorbium contains a major component on hydrocarbons, cellulose followed by alcohols, ketones, and aldehydes (Ouhaddou et al, 2022). According to the literature, hydrocarbons and some cellulose derivatives are characterized as nonionic polymers.…”
Section: Discussionmentioning
confidence: 99%
“…These plant species are characterized by the presence of several compounds, namely, proteins, polysaccharides, phenol and flavonoids substances, cellulose, and pectin (Madhu et al, 2020; Ouhaddou et al, 2022; Rostami‐Vartooni et al, 2016), which have been proven in the literature to exhibit a coagulant effect allowing their application to remove algal cells and organic matter (El Bouaidi et al, 2022; Graham et al, 2010; Kebaili et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectra were scanned in the range of 40-500 amu. Essential oil compounds were identified by matching unknown spectra with those reported in NIST08, NIST27, NIST147, NIST11, Wiley7N2; and on comparison of retention indices (RI) relative to retention times of a series of n-hydrocarbons (C7-C30) with those reported in the literature [67,68]. The percentage composition of the essential oils was computed by the normalization method from the GC peak areas.…”
Section: Analysis Of Essential Oils By Gc-ms and Gc-fidmentioning
confidence: 99%
“…Weeds disturbed sites may be toxic or irritant or pose some other danger to animals or humans. Weeds may harbor diseases, insect pests or vermin (Ouhaddou et al, 2022). They can impede regeneration of desired plants through allelopathic, suppressing their germination because of their physiological presence.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the increase of weeds resulted in the increase of the herbicide uses. However, these chemical products caused dangerous several effects notably food residues, unpleased side effects and resistance weeds against synthetic agents (Ouhaddou et al, 2022). This has encouraged researchers to look for new alternative pesticides more efficient and respectful to human and environment.…”
Section: Introductionmentioning
confidence: 99%